An Updated Review on the Role of Ginseng and Thyme Vulgaris in the Prevention and Control of Avian Viral Diseases with a Special Reference to Newcastle Disease Virus - Ahmed El- Sebai; Hesham A. Khalifa; Sabry Abd El-Motaal; Ola Hassanin (Journal of Advanced Veterinary Research, 2022)
Because of the growing dangers of viral infections, the use of herbal plant oils is gaining popularity among medical practitioners and large-scale livestock producers. Several studies have shown that herbal extracts could be used as an antiviral agent in animal feed or as a prophylaxis and remedy. Herbs, in addition to being a less expensive and safer alternative, may reduce the incidence of drug resistance and may modulate the immune system in the prevention of viral-related diseases. The main topic of this review is to focus on the antiviral and immunomodulatory potentials of thyme vulgaris and Ginseng, as well as their bioactive chemical components. The beneficial roles of the two herbaceous plant and their extracts upon avian viruses proofed in many earlier reports. Hence, the two herbs could have immune stimulant, antioxidant and anti-inflammatory benefits as well as adjuvant effects with poultry vaccines.